(untitled) (Cadernos de Sociomuseologia, 2019)
This article is the result of action research conducted during the postdoctoral research at the Department of Social Museology of the Lusophone University of Humanities and Technologies and the Center for Social Studies at the University of Coimbra, CES-UC, and presents the mobilization against the removal of “6 de Maio neighborhood”, located in Amadora, Lisbon Metropolitan Area, next to the social movement for the Right to Housing. The context is the transformation of the city into the “Lisbon of fashion”, which causes real estate valuation processes and takes on new meanings within the framework of the neoliberal logic of urban management. The consequences are assisted in the accelerated process of population replacement, triggered in certain areas of the city and the metropolitan region, which causes material and symbolic impacts to those affected. The article presents the “Memory Workshops” held in the “6 de Maio neighborhood” as a social movement strategy to trigger popular memory and boost the struggle for the right to housing. We sought to explore new forms of creative and affective resistance capable of acting in symbolic and immaterial spheres. Keywords: Memory Workshops; 6 de Maio, Amadora, Lisbon; Right to the city